Entrizee- A QR based Digital Gate Security Management System - Jarali, Ashwini; Kodilkar, Snehal; Tondare, Shubam; Kudale, Ganesh; Patel, Siddharth (International Journal of Computer Sciences and Engineering, 2025)
Security management systems in colleges, flats and gated communities have forever been supportedarchaic pen and paper system. Security guards pay most of their time in holding the records. Entrizee is an intelligentSecurity Management for Gated Premises that automates and computerizes manual tasks at the main gate(s). This system will be designed to maximize the security by providing an app to assist in entering the details of the user, keeping the records and perform analytics on it, which would otherwise have to be performed manually. Remaining straightforward to grasp and use, the system will meet the user’s expectations of minimizing the time required at the gates for physically entering all the details. It would also help the gatekeepers to keep a track of the people who are coming or leaving the premises after a certain specified time duration and take actions on them accordingly.